Innovations for plant production in the risky environment of semiarid Niger: a multilevel modeling assessment - Abele, S. (2004)
The paper deals with the problem of economically sustainable technological innovation for agriculture in the risky environment of Niger’s Sahelian zone smallholders. For these farmers, low-input mineral fertiliser technologies have been developed in the nineties in order to increase the productivity of their millet farming systems. As economic assessment cannot be restricted to plot or farm assessment alone but has to take into account also markets and marketing patterns, a sequence of models has been applied: On plot level, production functions of intercropping systems were estimated, in order to determine yields and their variability of the major crops. These data were fed in a Markowitz-Portfolio-model type by means of nonlinear programming to test the innovations, first at stable prices, then at declining prices that were obtained from an interregional trade model. The latter was shocked by the excess obtained from the yield gains of the innovations. This shock was depicting the sales from farmers even at declining prices, when they have to cover their costs of production, especially the fertiliser they used when applying the proposed innovations. The results show that due to risk aversion and high price volatility of output markets, farmers adopt mineral fertiliser innovations to a lesser degree than expected. Instead of that, they switch to other low-input techniques, like field management, that require less financial inputs.